2008
DOI: 10.1086/587171
|View full text |Cite
|
Sign up to set email alerts
|

Hinode SOT Observations of Solar Quiescent Prominence Dynamics

Abstract: We report findings from multihour 0.2Љ resolution movies of solar quiescent prominences (QPs) observed with the Solar Optical Telescope (SOT) on the Hinode satellite. The observations verify previous findings of filamentary downflows and vortices in QPs. SOT observations also verify large-scale transverse oscillations in QPs, with periods of 20-40 minutes and amplitudes of 2-5 Mm. The upward propagation speed of several waves is found to be ∼10 km s , comparable to the sound speed of a 10,000 K plasma, implyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
246
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(271 citation statements)
references
References 21 publications
24
246
1
Order By: Relevance
“…This is supported both by observations (e.g., Berger et al 2008;Lin et al 2005) and MHD simulations (e.g., Low & Petrie 2005). The effect of the increased penetration of the incident radiation, using multiple layer modelling, was also shown in 1D by Gouttebroze et al (2002).…”
Section: D Multi-thread Modelssupporting
confidence: 77%
“…This is supported both by observations (e.g., Berger et al 2008;Lin et al 2005) and MHD simulations (e.g., Low & Petrie 2005). The effect of the increased penetration of the incident radiation, using multiple layer modelling, was also shown in 1D by Gouttebroze et al (2002).…”
Section: D Multi-thread Modelssupporting
confidence: 77%
“…Observational evidence of the time damping of small amplitude oscillations in prominences has been reported by Landman (1977), Tsubaki & Takeuchi (1986), Tsubaki (1988), Wiehr et al (1989), Molowny-Horas et al (1999), Terradas et al (2002), Lin (2004), Berger et al (2008) and Ning et al (2009a,b). MolownyHoras et al (1999) and Terradas et al (2002) studied twodimensional time series from a quiescent prominence and found that oscillations detected in large areas of the prominence were typically damped after 2−3 periods.…”
Section: Introductionmentioning
confidence: 83%
“…Also, the presence in filaments of oscillating absorbing features which, at the same time, move along the filament axis has been reported (Lin 2004). In limb prominences different kinds of flows are observed (Chae et al 2008;Schmieder et al 2010) and, for instance, observations made by Berger et al (2008) with Hinode/SOT pointed out a complex dynamics with vertical downflows and upflows. In this case, velocities seem to be slightly higher than in filaments (up to 35 km s −1 ) and the orientation with respect to the magnetic field is unclear (Chae et al 2008;Schmieder et al 2010;Labrosse et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Locally, they consist of fine and vertically oriented plasma structures, so-called threads, that evolve continually (e.g., Engvold 1976;Zirker et al 1994). Recent ob-A movie is available in electronic form at http://www.aanda.org 1 There are many papers about solar prominences, but we recommend that the reader first go through the historical work of Einar Tandberg-Hanssen (e.g., Tandberg-Hanssen 1998, 2011 servations taken with the Hinode satellite have revolutionized our knowledge of the fine-scale structuring and dynamics of quiescent prominences; for instance, plasma oscillations, supersonic downflows, or plasma instabilities like the Rayleigh-Taylor instability in prominence bubbles (Berger et al 2008(Berger et al , 2010Chae et al 2008;Okamoto et al 2007). …”
Section: Introductionmentioning
confidence: 99%